Water Operators from Emerging Markets : New Players for Public-Private Partnerships - Marin, Philippe; Izaguirre, Ada Karina; Danilenko, Alexander (World Bank, Washington, DC, 2012)
In the 1990s a few multinationals dominated the market for public-private partnership (PPP) contracts in water. Yet in recent year's water operators from developing countries have won most of the new PPP contracts for the management of water utilities in countries as diverse as Brazil, Cameroon, Chile, China, Colombia, India, Malaysia, and the Russian Federation. While the size of the market served by large foreign operators has remained stagnant since 2001, the population served by private operators from developing countries grew from 15 million to more than 70 million, or 40 percent of the market, by 2008. This big shift opens new perspectives on using PPPs as a tool to reform water utilities in the developing world.